2020
DOI: 10.7759/cureus.7110
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Remission and Substantial Body Weight Reduction Achieved with Metformin and a Sodium-Glucose Cotransporter 2 Inhibitor

Abstract: The overall goal in the treatment of type 2 diabetes mellitus (T2DM) is remission. However, the effects of a sodium-glucose cotransporter 2 inhibitor (SGLT2i) on remission of T2DM are unknown. We herein report a case involving an overweight 43-year-old man who completely recovered from T2DM after SGLT2i therapy (dapagliflozin at 5 mg/day). In the pretreatment period, he had a body mass index (BMI) of 26.0 kg/m 2 , hemoglobin A1c (HbA1c) concentration of 10.3%, advanced insulin resistance, pancreatic β-cell dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…We found that his antibody titer to glutamic acid decarboxylase was undetectable (<5.0 U/mL) and his daily urinary C-peptide immunoreactivity (CPR) excretion was unexpectedly accelerated at 182.07 µg/day, thus establishing a definitive diagnosis of T2DM (Table 4). After admission, we provided the hospitalized dietary (1800 Kcal/day) and exercise therapies according to our standard protocol [8]. On the second day of hospitalization (before treatment), his blood glucose levels were still elevated under the optimal dietary therapy (Table 5).…”
Section: Table 3: Glucose and Insulin Concentrations In 75-g Oral Glumentioning
confidence: 99%
See 2 more Smart Citations
“…We found that his antibody titer to glutamic acid decarboxylase was undetectable (<5.0 U/mL) and his daily urinary C-peptide immunoreactivity (CPR) excretion was unexpectedly accelerated at 182.07 µg/day, thus establishing a definitive diagnosis of T2DM (Table 4). After admission, we provided the hospitalized dietary (1800 Kcal/day) and exercise therapies according to our standard protocol [8]. On the second day of hospitalization (before treatment), his blood glucose levels were still elevated under the optimal dietary therapy (Table 5).…”
Section: Table 3: Glucose and Insulin Concentrations In 75-g Oral Glumentioning
confidence: 99%
“…Because of the preserved capacity of endogenous insulin secretion from pancreatic β-cells and the absence of insulin resistance, the patient initially received lifestyle modification therapy with stopping smoking and drinking, taking adequate calorie intake, reducing salt intake, and introducing an exercise habit during the hospitalized treatments [8]. He also received an explanation for his diabetic conditions and his novel pathogenesis of hyperglycemia with elevated insulin clearance.…”
Section: Table 3: Glucose and Insulin Concentrations In 75-g Oral Glumentioning
confidence: 99%
See 1 more Smart Citation
“…These effects were observed in spite of the discontinuation of all glucose-lowering medications. This real-world clinical evidence demonstrated that diabetes remission and normal body weight could be effectively achieved in persons with newly diagnosed T2DM by a combination therapy of metformin and SGLT2i [ 48 ].…”
Section: Role Of Medications In Achieving T2dm Remissionmentioning
confidence: 99%
“…In addition to decreasing blood sugar levels, metformin is emerging as a therapy with other numerous beneficial effects, including body weight control; reductions in the incidence of aging-related diseases; reductions in the risks of cardiovascular and neuropsychiatric disorders and metabolic syndrome; and even improving fertility in polycystic ovary syndrome (PCOS) [ 4 , 5 , 6 , 7 ]. Recent literature data describe metformin as an endothelial protector, an effective drug in heart failure, and an anti-inflammatory target useful in rheumatological and immunological diseases as well as in many aging-related morbidities [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%